2023
DOI: 10.3390/v15122296
|View full text |Cite
|
Sign up to set email alerts
|

Shiftless Is a Novel Member of the Ribosome Stress Surveillance Machinery That Has Evolved to Play a Role in Innate Immunity and Cancer Surveillance

Jamie A. Kelly,
Jonathan D. Dinman

Abstract: A longstanding paradox in molecular biology has centered on the question of how very long proteins are synthesized, despite numerous measurements indicating that ribosomes spontaneously shift reading frame at rates that should preclude their ability completely translate their mRNAs. Shiftless (SFL; C19orf66) was originally identified as an interferon responsive gene encoding an antiviral protein, indicating that it is part of the innate immune response. This activity is due to its ability to bind ribosomes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Finally, our study suggests that SFL can interfere with HIV-1 infection without inhibiting −1PRF. Recent work by the Dinman group has shown that SFL overexpression leads to a reduction in mRNA abundance of both reporter and endogenous cellular mRNAs [ 51 ]. It is conceivable that the various SFL mutants that we have analyzed could impact gag-pol mRNA levels in a different way, possibly due to variable extents of mRNA binding or recruitment of mRNA surveillance proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study suggests that SFL can interfere with HIV-1 infection without inhibiting −1PRF. Recent work by the Dinman group has shown that SFL overexpression leads to a reduction in mRNA abundance of both reporter and endogenous cellular mRNAs [ 51 ]. It is conceivable that the various SFL mutants that we have analyzed could impact gag-pol mRNA levels in a different way, possibly due to variable extents of mRNA binding or recruitment of mRNA surveillance proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, other modes of action are possible, including interference with the expression of other viral proteins, such as Env. Furthermore, a recent study has shown that both SFL overexpression and depletion can reduce the abundance of reporter mRNAs, independent of whether they possess an FSE [ 128 ]. Although it is important to note that this study was carried out with frameshift reporter systems rather than with authentic viruses [ 128 ], this finding may suggest that SFL plays a role in modulating RNA stability and might be involved in cellular RNA decay pathways, as described in the context of other viral infections [ 97 , 99 ].…”
Section: Shiftless Targets Mrna Recoding Mechanismsmentioning
confidence: 99%